Academic Management Responding to Changes in the VUCA World Based on Sikkhā 3 (The Threefold Training) - Lertprawat, Anuwat (ASEAN Journal of Religious and Cultural Research, 2024)
Academic management in educational institutions during the VUCA World requires adaptation and development to respond to rapid and uncertain changes. Specifically, applying the principles of Sikkhā 3 (the Threefold Training)—Sīla (Morality), Samādhi (Concentration), and Paññā (Wisdom)—can strengthen and enhance the resilience of educational institutions effectively, utilizing the principle of Morality in academic management fosters a culture of ethical conduct and builds trust within the organization, promoting Concentration enables personnel to focus on critical tasks, while developing Wisdom allows administrators to analyze and make reasoned decisions in complex situations. Therefore, integrating the principle of Sikkhā 3 (the Threefold Training) into academic management is a crucial tool for achieving success in educational institutions in this transformative era.